2019
DOI: 10.1039/c8em00431e
|View full text |Cite
|
Sign up to set email alerts
|

Differences in photochemistry between seawater and freshwater for two natural organic matter samples

Abstract: NOM displays different photochemistry in seawater than in freshwater due to its complexation with Mg2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
1
15
1
Order By: Relevance
“…Further studies using complimentary techniques are needed to validate these findings, given the limitations of this study. It has been shown previously that NOM reactivity, via the formation of singlet oxygen, decreases in the presence of metals, 56,68,92 so the results of this study show that this decrease is not due to conformational changes affecting the ability of ground state oxygen to quench the excited triplet. We also showed that the analysis performed in this study, although very simplified, is applicable to both fluorescence quenching and enhancement interactions.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Further studies using complimentary techniques are needed to validate these findings, given the limitations of this study. It has been shown previously that NOM reactivity, via the formation of singlet oxygen, decreases in the presence of metals, 56,68,92 so the results of this study show that this decrease is not due to conformational changes affecting the ability of ground state oxygen to quench the excited triplet. We also showed that the analysis performed in this study, although very simplified, is applicable to both fluorescence quenching and enhancement interactions.…”
Section: Discussionsupporting
confidence: 60%
“…Many metals can quench NOM fluorescence, especially via formation of nonfluorescent NOM-metal complexes. 19,29,30,[47][48][49][50][51][52] By contrast, some metals, such as Ca 2+ , Al 3+ , and Mg 2+ , enhance the fluorescence of NOM; 22,26,[53][54][55][56] this is also thought to be due to the formation of complexes that may enhance the rigidity of NOM. 51,57,58 In general, complexation with metals is thought to change the conformation of NOM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of sea salts (NaCl, NaBr, and NaI) can eventually influence the photochemical process of FL/DMSO at the sea surface (Grossman et al, ; Stirchak et al, ). Ongoing studies in our lab are focused on the influence of sea salts on photochemical degradation of FL/DMSO, and the results will be published elsewhere.…”
Section: Discussionmentioning
confidence: 99%